Skin care of geriatric patients - Stanislovienė, Nereta (Slauga. Mokslas ir praktika, 2021)
The aim – to analyze the scientific literature of skin problems of the elderly and provide recommendations for skin care of geriatric patients.The number of older people is growing every year around the world and evolving medical and nursing care are making possible to live longer. However, aging individuals are more likely to experience a variety of problems and chronic illnesses. These individuals also often cannot avoid skin problems such as dermatitis caused by decreased skin protective function, dry skin or incontinence. Due to physiological changes seen with aging skin as well as disease-induced alterations in old age, proper skin care of geriatric patients becomes an important and significant element of nursing and foundations for the well-being and quality of life of the elderly.31 sources of literature are analyzed.The search was performed using keywords: elderly, dry skin, incontinence-induced dermatitis, skin care of geriatric patients, skin moisturizers.After reviewing the scientific papers, recommendations are presented of geriatric patients' skin care.The article is intended for nurses, health care and social sector workers caring for the elderly, and researchers
Keywords: elderly; dry skin; incontinence-induced dermatitis; skin care of geriatric patients; skin moisturizers